2020
DOI: 10.1177/1362361320934230
|View full text |Cite
|
Sign up to set email alerts
|

Service use by youth with autism within a system-driven implementation of evidence-based practices in children’s mental health services

Abstract: Public mental health systems play an important role in caring for youth with autism spectrum disorder. Like other dually diagnosed populations, youth with autism spectrum disorder may receive services in the context of evidence-based practice implementation efforts within public mental health systems. Little is known about service use patterns within the context of system-driven implementations efforts for this population. This case–control study examined mental health service patterns of 2537 youth with autis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Screening results indicated that children in our sample had elevated scores on the Attention and Externalizing but not Internalizing subscales of the PSC-17. The high positive screen rate and the pattern of mental health need types are consistent with research reporting high rates of co-occurring mental health conditions for children with autism and the common co-occurrence of challenging behaviors, which includes both attention and externalizing symptoms, for these youth (Brookman-Frazee et al, 2018; Stadnick, Lau, et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Screening results indicated that children in our sample had elevated scores on the Attention and Externalizing but not Internalizing subscales of the PSC-17. The high positive screen rate and the pattern of mental health need types are consistent with research reporting high rates of co-occurring mental health conditions for children with autism and the common co-occurrence of challenging behaviors, which includes both attention and externalizing symptoms, for these youth (Brookman-Frazee et al, 2018; Stadnick, Lau, et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…For example, our findings indicated that children in our sample did not evidence elevations on the Internalizing subscale of the PSC-17. While challenging behaviors are the most common mental health need in school-age children with ASD (Brookman-Frazee et al, 2018; Stadnick, Lau, et al, 2020), there is potential that caregivers under-reported internalizing symptoms because they can be difficult to recognize.…”
Section: Discussionmentioning
confidence: 99%
“…Some highlighted the significant ramifications diagnostic overshadowing had in terms of the resources and legal recourse made available to them, while others reflected that not recognizing signs of coping caused themselves, educators, and healthcare workers to miss opportunities to intervene at the peak of their child's distress. These observations are consistent with studies documenting the reduced provision of trauma-focused treatments to autistic versus non-autistic youth, as well as a desire for training in trauma identification and treatment amongst autism-focused providers ( 29 , 84 ). Similarly, autistic adults reflected on how their attempts to cope could be dismissed as part of their autism diagnosis.…”
Section: Discussionsupporting
confidence: 88%
“…Yet, in a recent study of community ASD providers in the US (Kerns, Berkowitz, et al, 2020), >75% agreed that trauma assessments are warranted for autistic youth and over half reported screening and treating trauma symptoms in their autistic clients despite a professed need for further training. Stadnick et al (2020) found that autistic children were significantly less likely than those not on the spectrum to receive trauma services in a US public mental health system-a disparity, which may also reflect the limited evidence available to guide trauma services in this group. As such, experts in this study represent a rare and specialized cohort, whose insights may help address the high demand for clinical knowledge in this area and guide future research.…”
Section: Discussionmentioning
confidence: 98%
“…Stadnick et al. (2020) found that autistic children were significantly less likely than those not on the spectrum to receive trauma services in a US public mental health system–a disparity, which may also reflect the limited evidence available to guide trauma services in this group. As such, experts in this study represent a rare and specialized cohort, whose insights may help address the high demand for clinical knowledge in this area and guide future research.…”
Section: Discussionmentioning
confidence: 99%